Dialogue therapy for couples and real dialogue for opposing sides : methods based on psychoanalysis and mindfulness /: methods based on psychoanalysis and mindfulness. (2021) - Pieniadz, Jean, 1956-; Young-Eisendrath, Polly, 1947-
No abstract available